Immunomodulatory effects of amniotic membrane matrix incorporated into collagen scaffolds - Hortensius, Rebecca A. (J Biomed Mater Res A, 2016)
Adult tendon wound repair is characterized by the formation of disorganized collagen matrix which leads to decreases in mechanical properties and scar formation. Studies have linked this scar formation to the inflammatory phase of wound healing. Instructive biomaterials designed for tendon regeneration are often designed to provide both structural and cellular support. In order to facilitate regeneration, success may be found by tempering the body’s inflammatory response. This work combines collagen-glycosaminoglycan scaffolds, previously developed for tissue regeneration, with matrix materials (hyaluronic acid and amniotic membrane) that have been shown to promote healing and decreased scar formation in skin studies. The results presented show that scaffolds containing amniotic membrane matrix have significantly increased mechanical properties and that tendon cells within these scaffolds have increased metabolic activity even when the media is supplemented with the pro-inflammatory cytokine interleukin-1 beta. Collagen scaffolds containing hyaluronic acid or amniotic membrane also temper the expression of genes associated with the inflammatory response in normal tendon healing (TNF-α, COLI, MMP-3). These results suggest that alterations to scaffold composition, to include matrix known to decrease scar formation in vivo, can modify the inflammatory response in tenocytes.